Faktor Penyumbang Terhadap Pencapaian Sifar Ujian Penilaian Sekolah Rendah di Sarawak - Abdul Said Ambotang; Baharom Mohamad; Mohd Yusof Abdullah; Mohd Suhaimi Taat; Roslee Talip (Penerbit UTM Press, 2012)
This study was conducted to determine the contributing factors towards Primary School Evaluation Test (UPSR) zero achievement in selected schools. The study involved many factors that affected school UPSR result which eventually led to zero achievement (0%). The lowest result had generated negative perception that school authority especially teachers had not taught copiously. In this case, findings showed failure or success of pupils in academic and UPSR not only depended on teacher’s efforts but involved all related authorities including Education Department, school leaders, teachers, pupils, parents and others in a unique and holistic way. Therefore, to overcome this unhealthy phenomenon, each party or individual needs to conduct self-reflect activities followed by improvement action which not only has positive impact on oneself but every individual involved.